Cross-border shopping: examining motivations from the perspective of Bruneian visitors in Limbang, Malaysia - Thirunaukarasu Subramaniam; Evelyn S. Devadason; Sivachandralingam Sundararaja (Penerbit Universiti Kebangsaan Malaysia, 2013)
A tourism generating activity that is becoming increasingly important in border-towns of Malaysia is cross-border shopping. The present study investigates the cross-border shopping behavior of Bruneian visitors in Limbang, Sarawak, Malaysia. The objective is to profile the demographic characteristics of the visitors; their spending patterns; and analyze the motivating factors for cross-border shopping. The present study makes three principal findings. First, most of the Bruneian cross-border shoppers are found to be day trippers from the lower income group. Second, the analyses reveal that the purchasing behavior of day trippers differs from that of short-term visitors. The former tends to spend more on food and beverages, whilst the latter are attracted to services in Limbang, such as entertainment outlets. Third, the three major motivating factors from the nine underlying dimensional influences of Brunei-Limbang cross-border shopping are the favourable exchange rate; the various/reliable services available; and the retail atmosphere, which are compensated for by the safe and easy access to Limbang and the low transport costs associated with the travel.